2006
DOI: 10.1007/s10509-006-9189-6
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Reaction-Diffusion Equations

Abstract: Abstract. In a series of papers, Saxena, Mathai, and Haubold (2002, 2004a, 2004b) derived solutions of a number of fractional kinetic equations in terms of generalized Mittag-Leffler functions which provide the extension of the work of Mathai (1995, 2000). The subject of the present paper is to investigate the solution of a fractional reaction-diffusion equation. The results derived are of general nature and include the results reported earlier by many authors, notably by Jespersen, Metzler, and Fogedby (1999… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
53
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 31 publications
8
53
0
Order By: Relevance
“…In recent years, there has been a great deal of interest in fractional reaction-diffusion (FRD) systems [26][27][28][29][30][31][32][33][34][35] which from one side exhibit self-organization phenomena and from the other side introduce a new parameter to these systems, which is a fractional derivative index, and it gives a greater degree of freedom for diversity of self-organization phenomena. At the same time, the process of analyzing such FRD systems is much more complicated from the analytical and numerical point of view.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a great deal of interest in fractional reaction-diffusion (FRD) systems [26][27][28][29][30][31][32][33][34][35] which from one side exhibit self-organization phenomena and from the other side introduce a new parameter to these systems, which is a fractional derivative index, and it gives a greater degree of freedom for diversity of self-organization phenomena. At the same time, the process of analyzing such FRD systems is much more complicated from the analytical and numerical point of view.…”
Section: Introductionmentioning
confidence: 99%
“…The interpretation of the parameter μ in Eqs. (21) and (26) deserves some discussion. Eventhough the term "−μφ" looks like a "damping", its role is exactly the opposite.…”
Section: Tempered Fractional Diffusionmentioning
confidence: 99%
“…[8], where it was shown that the truncation of the Lévy flights due to tempering leads to a transient front acceleration after which the front asymptotically reaches a terminal speed. Other works on anomalous transport in front propagation include studies on: bistable reaction processes and anomalous diffusion caused by Lévy flights [25]; analytic solutions of fractional reaction-diffusion equations [21]; reaction-diffusion systems with bistable reaction terms and directional anomalous diffusion [15]; construction of reaction-sub-diffusion equations [22]; fractional reproduction-dispersal equations and heavy tail dispersal kernels [1]; role of fluctuations in reaction-super-diffusion dynamics [2]; non-Markovian random walks and sub-diffusion in reaction-diffusion systems [13]; exact super-diffusive front propagation solutions with piecewise linear reaction kinetics functions [24]; and front dynamics in two-species competition models driven by Lévy flights [14], among others. The recent work in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…This paper summarizes briefly a research programme, comprised of five elements: (i) standard deviation analysis and diffusion entropy analysis of solar neutrino data [1,2]; (ii) Mathai's entropic pathway model [3,4]; (iii) fractional reaction and extended thermonuclear functions [5,6]; (iv) fractional reaction and diffusion [7,8]; and (v) fractional reaction-diffusion [9][10][11][12]. Boltzmann translated Clausius' second law of thermodynamics "The entropy of the Universe tends to a maximum" into a crucial quantity that links equilibrium and non-equilibrium (time dependent) properties of physical systems and related entropy to probability, S = k log W, which, later, Einstein called Boltzmann's principle [13].…”
Section: Introductionmentioning
confidence: 99%